Assessment on halal status of antibiotic and antifungal products at Hopital Sungai Buloh / Suryawaty Muhammad - Muhammad, Suryawaty (2015)
Muslim consumers are progressively mindful and in search for Halal medicines. In hospital setting especially Hospital Sungai Buloh as Infectious Disease Centre, antibiotic and antifungal products are among the most common used. But, the Halal status of each product used is unknown. This study is intended to determine the status of Permissible/Halal or' Shariah' comply of the antibiotic and antifungal products in Sungai Buloh Hospital. Antibiotic and antifungal products are composed of a combination of active ingredients, and inactive ingredients (excipients). These ingredients are obtained from a variety of sources; animals, plants or synthetic origin. Assessment to the products only based on product leaflets provided by pharmaceutical companies and used academic and other websites references. From this study, 90 products have been assessed, of these 18.9% permissible, 1.1% forbidden, 21.1% doubtful and 58.9% unknown. The compound in inactive ingredient that cause of forbidden is from alcohol. Meanwhile, the most common compound that cause of doubtful in active (100.0%) and inactive ingredients (69.6%) are from animal or plant or synthetic. More than half (58.9%) of the products cannot be assessed due to incomplete data from product leaflets especially for inactive ingredients. For the conclusion, all parties such as Ministry of Health, Pharmaceutical companies, health care professional and others should play their role to provide only permissible medicine for Muslim consumers to comply their religion.